Improving Eighth Grade Students’ English Vocabulary Mastery Through Song Based Multisensory Instruction at SMPN 2 Dusun Selatan - Pahridafriatin; Ari Purnama (Universitas Islam Negeri Palopo, 2026)
This classroom action research examined whether song-based multisensory instruction could improve the English vocabulary mastery and classroom participation of eighth-grade students at SMPN 2 Dusun Selatan. The study was initiated because preliminary observations showed low vocabulary achievement, limited motivation, anxiety, and passive participation under predominantly teacher-centered instruction. The intervention used Maywood’s “Mother, How Are You Today?” together with visual aids and interactive games. The Kemmis and McTaggart action research cycle was implemented across three cycles, each comprising planning, action, observation, and reflection, with 32 students. Data were collected through vocabulary tests, classroom observations, and semi-structured interviews. Quantitative data were summarized using mean scores and the percentage of students meeting the Minimum Mastery Criterion of 75, while qualitative data were analyzed through data condensation, data display, and conclusion drawing. The reported mastery percentage increased from 16% in the pre-action test to 40% in Cycle I, 65% in Cycle II, and 85% in Cycle III. The class mean increased from 58 before the intervention to 85 at the end of Cycle III. Classroom observations also indicated greater participation, confidence, and willingness to practice pronunciation and sentence construction. These findings indicate that, in this class, combining a familiar song with visual and kinesthetic support was associated with improved vocabulary achievement and a more active learning environment. Because the study involved one class and descriptive analysis, the findings should be interpreted within the local classroom context.